Identifying Key Drivers of Repurchase Intentions for Sari Roti Products Using Binary Logistic Regression Analysis - Annisa Liestiani; Ayu Wulandari; E. N. Budiyanto Hariandja; Jerry Heikal (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This study aims to analyze various factors that influence the repurchase decision of Sari Roti products. The method used in this research is binary logistic regression using the SPSS tool. A sample of 156 consumers was randomly selected. Data was collected through a survey filled out by 156 Sari Roti consumers. The survey results were entered into Microsoft Excel and then normalized. For Independent Variable and Dependent Variable data in the form of text "Yes" or "No", it will be converted into binary numbers, meaning it is represented by the numbers 1 (one) and 0 (zero). Independent Variable data consists of Durability, Reliable Quality, Well-Known Brand, Prestigious Brand, Interested In New Flavors, New And Innovative Products, Sufficiently Many Variants, Affordable Price, Competitive Price, Price Matches The Quality, Value For Money, Promotion Via Facebook, Promotion Via Instagram, Promotion Via Twitter, Promotion Via YouTube, and Promotion Via Website, Influencer Recommendation, Family Recommendation, Friend Recommendation, Good Memory Or Experience, Easily Accessible Store Location, Always Available, Satisfied With Customer Service, Good Reputation, Easy-To-Remember Brand, Good Packaging Condition. While, the Dependent Variable is the Repurchase Intentions. From the research results, it can be concluded that the factors that significantly influence the repurchase decision are Prestigious Brand, Sufficiently Many Variants, and Affordable Price. Other variables do not significantly affect the decision to repurchase Sari Roti products. Based on the binary logistic regression analysis of 156 Sari Roti consumers, it was predicted that 140 consumers would repurchase, and 16 consumers would not, with a data accuracy of 83.3%.